Leksikon Makanan Jalanan Asal Luar Negeri di Kota Mojokerto: Kajian Etnolinguistik - Fatimatus Zahro; Ragil Sri Wahyuningsih; Taswirul Afkar (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
This research aims to identify and describe the lexicon in the names of foreign street foods in Mojokerto City. The research method used by researchers is a descriptive qualitative method which aims to find data that falls into the category of street food from abroad to be analyzed in the lexicon aspect. The data collection technique used by researchers is the reading and recording technique by reading carefully from various sources, then recording the findings for analysis. The results of the research show that there are 15 names of street food from abroad in the city of Mojokerto. The names of these street foods come from various countries, such as China, Japan, Korea, the Middle East, Italy, and so on. Apart from that, from the results of the lexicon analysis, it was found that 8 data were in the form of words, and 7 data were In the form of nouns, 1 data was in the verb type, 1 data was in the adjective category, and 7 data were in the form of phrases which were in the noun phrase type.